ANALISIS PENGEMBANGAN INVESTASI PRODUKSI BENIH JAGUNG HIBRIDA DI KOTA SOLOK - Hanifah, Ryan Azmii; Krisnamurthi, Bayu; Herawati, Herawati (Jurnal Agribisnis Indonesia, 2023)
One way to fulfill the corn supply is by increasing productivity using superior seeds such as hybrid corn seeds. PT Agricorn Putra Sejati is a producer of hybrid corn seeds that plans to expand its production capacity. This research aims to determine the feasibility of business development and analyze the maximum changes in fertilizer prices and permanent labor wages. The study uses scenarios : scenario 0 (condition without development), scenario I (development condition with a labor-intensive system), and scenario II (development condition with more machine usage). The research considers non-financial aspects (market aspects, technical aspects, management and legal aspects, social, economic, and cultural aspects, as well as environmental aspects), financial aspects (NPV, Net B/C, IRR, Payback Period), and replacement value analysis. A company will be considered viable if NPV >0, Net B/C >1, IRR >1, and Payback Period >business life. The results show that the company is feasible to develop and will obtain a higher net benefit if using scenario II. Based on the replacement value analysis, the company is more sensitive to an increase in labor wages than an increase in fertilizer prices.